Experimental and numerical multiscale approach to thermally cycled FRP. (15th July 2020) - Lüders, Caroline; Kalinka, Gerhard; Li, Wei; Sinapius, Michael; Wille, Tobias
Abstract: Due to the different thermal expansion of the constituent materials, cyclic thermal loading of FRP induces alternating stresses in the material at two scales: at the micro scale (level of fibre–matrix-interaction) and at the macro scale (level of the multidirectional laminate). Especially the micro scale effect is not comprehensively investigated yet. Additionally, computational investigations mostly neglect this effect due to the homogenous modelling of the composite material. As this effect is assumed to significantly contribute to the fatigue of FRP at thermal loads, the present paper suggests an experimental and numerical multiscale approach including experiments at the different involved material scales to separately observe the effects acting at these scales. The approach also includes numerical modelling for each scale to complement the knowledge gained from the experiments and to create a basis for the consideration of the micro effect even in macroscopic fatigue models treating homogeneous modelled composites. The main focus of the contribution is to bring the overall approach up for discussion, rather than to present the multiscale modelling details.